PENGARUH KARAKTERISTIK INDIVIDU TERHADAP FIT TO WORK: KARAKTERISTIK - Sunardi; Mirasa, Yudied Agung (WELL BEING, 2024)
Background: Fit to work, or an individual's ability to perform job tasks effectively and safely, especially in jobs that require high concentration and physical skills such as heavy equipment operators, is influenced by several important characteristic factors, including age, sleep duration, and nutritional status.The objective of this study was to determine the influence of individual characteristics of heavy equipment operator workers on their fit to work. Subjects and Methods: This study employed an observational analytic design with a cross-sectional approach. The research was conducted at the Bagong Dam Project, Trenggalek, PT PP area, with using a total sampling technique of 48 heavy equipment operator workers. The independent variables were age, sleep duration, and nutritional status of workers, while the dependent variable influenced was fit to work. Data was collected through questionnaires and medical examinations. Data analysis was performed using logistic regression analysis at a significance level of 0.05. Results: The results indicate that age (p<0.782) does not significantly influence "fit to work" status, whereas sleep duration (p>0.037) demonstrates a significant impact. Nutritional status (p<0.488) shows no significant effect. Conclusion: It is recommended that the company focus on regulating adequate sleep for workers to improve health and safety at work.